2006
DOI: 10.2516/ogst:2006018x
|View full text |Cite
|
Sign up to set email alerts
|

Combustion and Exhaust Emissions in a Heavy-Duty Diesel Engine with Increased Premixed Combustion Phase by Means of Injection Retarding

Abstract: Résumé -Processus de combustion et émissions de polluants d'un moteur diesel de poids lourdfonctionnant avec une phase de combustion en prémélange augmentée par retard à l'injectionUne étude expérimentale a été réalisée sur un moteur diesel de poids lourd avec des systèmes d'injection et de combustion standard, fonctionnant à faible charge. L'objectif était de promouvoir, en retardant le début de l'injection, une phase de combustion en prémélange importante. Une analyse détaillée des caractéristiques de la com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…In addition, they found that CO and CO 2 emissions were significantly reduced by advancing the fuel injection timing. In contrast, those researchers indicated that diesel engines produce low levels of smoke opacity and NO x emissions when the fuel injection is retarded [11]. The effect of high fuel injection pressure and injection timing has been reported to reduce exhaust emissions from diesel engines.…”
Section: Introductionmentioning
confidence: 97%
“…In addition, they found that CO and CO 2 emissions were significantly reduced by advancing the fuel injection timing. In contrast, those researchers indicated that diesel engines produce low levels of smoke opacity and NO x emissions when the fuel injection is retarded [11]. The effect of high fuel injection pressure and injection timing has been reported to reduce exhaust emissions from diesel engines.…”
Section: Introductionmentioning
confidence: 97%
“…Common Rail Diesel Injection systems have led the technological renaissance (Badami et al, 1999;Suh, 2011) in diesel injection characteristics of the present day due to its efficacy in drastically reducing BSFC and the conventional PM emission precursors as compared to conventional diesel operation (Balusamy and Marappan, 2010;Nagata et al, 2004;Shimazaki et al, 2003;Pickett and Siebers, 2004;Minato et al, 2005). That said the very ability of the CRDI systems to decrease PM emissions has been found to be a penalizing precursor for NOx formation which have been observed to paradoxically increase (Badami et al, 1999;Desantes et al, 2004;Pierpont and Reitz, 1995;Payri et al, 2006) on account of higher peak temperature arising out of very lean and homogenous conditions which provide impetus for attaining close-to adiabatic flame temperatures during the ensuing combustion. To contain the consequence of NOx emissions while retaining the incentives of lower PM and fuel consumption on CRDI systems, EGR (Reitz, 1998;Ladommatos et al, 1998;Hountalas et al, 2008;Maiboom et al, 2008;Roy et al, 2014a;Bose et al, 2013) and pilot injection strategies (Buyukkaya and Cerit, 2008;Thurnheer et al, 2011) have been widely investigated.…”
Section: Introductionmentioning
confidence: 91%
“…The main idea of CFD method is to describe a continuous physical field by a set of variable collections, build their mathematical equations, and solve the approximate values of these variables. As a numerical method of the basic fluid governing equations, CFD can be used to determine the physical parameter values in a complex fluid field, such as the flow velocity patters, pressure distribution, and temperature distribution [9].…”
Section: Basic Theory Of Hydrokinetics and Thermodynamicsmentioning
confidence: 99%
“…Most of these works focused on experimental studies and attempted to get the thermodynamic parameters by test data processing [2], [3], [6]. A good review of EGR-related theoretical methods was performed in [7]- [9].…”
Section: Introductionmentioning
confidence: 99%